Multicentre survey of retinopathy of prematurity in Indonesia - J Edy Siswanto; Pieter J J Sauer; Peter H Dijk; Arend F Bos; Rinawati Rohsiswatmo; Gatot Irawan; Eko Sulistijono; Pertin Sianturi; Dewi A Wisnumurti; Rocky Wilar; Tetty Yuniati; Gatot Sarosa; et al. (BMJ Publishing Group, 2021)
Background The incidence of retinopathy of prematurity (ROP) is higher in Indonesia than in high-income countries. In order to reduce the incidence of the disease, a protocol on preventing, screening and treating ROP was published in Indonesia in 2010. To assist the practical implementation of the protocol, meetings were held in all Indonesia regions, calling attention to the high incidence of ROP and the methods to reduce it. In addition, national health insurance was introduced in 2014, making ROP screening and treatment accessible to more infants.Objective To evaluate whether the introduction of both the guideline drawing attention to the high incidence of ROP and national health insurance may have influenced the incidence of the disease in Indonesia.Setting Data were collected from 34 hospitals with different levels of care: national referral centres, university-based hospitals, and public and private hospitals.Methods A survey was administered with questions on admission numbers, mortality rates, ROP incidence, and its stages for 2016-2017 in relation to gestational age and birth weight.Results We identified 12 115 eligible infants with a gestational age of less than 34 weeks. Mortality was 24% and any stage ROP 6.7%. The mortality in infants aged less than 28 weeks was 67%, the incidence of all-stage ROP 18% and severe ROP 4%. In the group aged 28-32 weeks, the mortality was 24%, all-stage ROP 7% and severe ROP 4%-5%. Both mortality and the incidence of ROP were highest in university-based hospitals.Conclusions In the 2016-2017 period, the infant mortality rate before 32 weeks of age was higher in Indonesia than in high-income countries, but the incidence of ROP was comparable. This incidence is likely an underestimation due to the high mortality rate. The ROP incidence in 2016-2017 is lower than in surveys conducted before 2015. This decline is likely due to a higher practitioner awareness about ROP and national health insurance implementation in Indonesia.